Efficacy of perturbation-based balance training in anterior cruciate ligament tears. A systematic review - Marcos Méndez-Bouza; Alejandra Alonso-Calvete; Rocío Abalo-Núñez (Apunts Sports Medicine, 2023)
Anterior cruciate ligament (ACL) tear is a serious and debilitating injury with significant physical, psychological, and socioeconomic consequences. Perturbation-based balance training (PBBT) is a type of neuromuscular training that involves the manipulation of mobile support surfaces, using controlled, unpredictable, multidirectional forces, in order to perturb the balance of the trained individual and thus improve the efficiency of muscle contraction patterns and the dynamic stability of the lower extremity joints. The aim of this review is to analyze the efficacy of the PBBT as a neuromuscular re-education method of choice for the recovery of functional capacity in individuals with ACL knee rupture. A systematic search was carried out in PubMed, Cinahl, Cochrane Library, Medline, PEDro Physiotherapy Evidence Database, Scopus, Web of Science and Sport Discus during January 2022. Only randomized clinical trials conducted in humans and published in English or Spanish were considered. The methodological quality was assessed using the PEDro scale and the risk of bias using the Risk-of-Bias tool of The Cochrane.12 studies were included. In 3 of them, the intervention with PBBT took place before ACL reconstruction, in 7 after ACL reconstruction and in 2 the subjects did not undergo surgical intervention. PBBT appears to be effective in the non-surgical recovery, improving joint stability and neuromuscular control. It was also effective as a preoperative treatment in normalizing knee excursion after ACL surgery. In contrast, the evidence does not support its efficacy as the neuromuscular re-education method of choice in the return-to-sport phase in previously operated athletes.